2020
DOI: 10.1080/23802359.2020.1831984
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the black-winged fly, Felderimyia fuscipennis (Diptera: Tephritidae) and its phylogenetic relationship within family Tephritidae

Abstract: The black-winged fly, Felderimyia fuscipennis (Diptera: Tephritidae), is an insect pest of bamboo shoot, mainly distributed in Thailand, Malaysia and Yunnan Province and Guangxi Autonomous Region, China. The complete sequence of the mitogenome of F. fuscipennis has been determined in this study. The whole mitogenome sequence is 16,536 bp in length, which totally contains 13 protein-coding genes (PCGs), 2 rRNA genes, 22 tRNA genes, and a non-coding region (putative control region, CR). The phylogeny indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…In the present study, the phylogenetic relationships within Tephritidae can be presented as follows: ((Bactrocera, Dacus, Zeugodacus), Felderimyia, Anastrepha), (Acrotaeniostola, (Neoceratitis, Ceratitis), Euleia, Rivellia), (Procecidochares, (Tephritis, Sphaenisscus))))), in concordance with the findings of previous phylogenetic studies [23,24,63,64]. The results showed that four genera (Felderimyia, Zeugodacus, Dacus and Bactrocera) are closely related and they gathered to form a sister group.…”
Section: Disscusionsupporting
confidence: 91%
“…In the present study, the phylogenetic relationships within Tephritidae can be presented as follows: ((Bactrocera, Dacus, Zeugodacus), Felderimyia, Anastrepha), (Acrotaeniostola, (Neoceratitis, Ceratitis), Euleia, Rivellia), (Procecidochares, (Tephritis, Sphaenisscus))))), in concordance with the findings of previous phylogenetic studies [23,24,63,64]. The results showed that four genera (Felderimyia, Zeugodacus, Dacus and Bactrocera) are closely related and they gathered to form a sister group.…”
Section: Disscusionsupporting
confidence: 91%